Validation of the use of spectrophotometer (WYD iodine checker) for the determination of iodine in food salt - Carmelle, Mizehoun-Adissoda; Agueh, Victoire; YEMOA, Loconon Y. Achille; Segla, Boris; ALIHONOU, FLORENCE NATHALIE YACOBA; JOSSE, Roger Gérard; Houinato, Dismand; DESPORT, Jean-Claude; Bigot, André (My University, 2017)
The iodine content in food salt is generally determined qualitatively using rapid test kits or quantitatively by iodometric titration (reference method). Spectrophotometric analysis is one of the recent developed quantitative methods, which has the advantage of being simple, robust and more convenient for the laboratory technician. However, there are few comparative studies between this method and the reference method. The aim of this study was to evaluate the agreement between spectrophotometric and iodometric titration methods. From May to October 2013, 117 salt samples were collected in the households of Glazoué’s town (Benin), through a three-stage sampling. Samples were assayed by iodometric titration and by a portable spectrophotometer (WYD Iodine Checker). The agreement between results of the two methods was performed using Bland-Altman plots. The mean levels of iodine in salt samples were 28.2±14.0 and 28.4±14.0 ppm by iodometric titration and spectrophotometry respectively. There is an excellent correlation between the results of both methods (r= 0.97, p< 0.001). The agreement between the two methods gave a mean difference of d= 0.2 ppm, within the limits: d ± 2 sd= -6.2 and 6.5 ppm. This study showed that the spectrophotometric method can replace the iodometric titration for iodine analysis in dietary salt. This method is more convenient, uses simple laboratory procedures and can be popularized.
Keywords: Spectrophotometry; Iodometric titration; food salt; Iodine.